Open schools: effects on parental engagement and information asymmetry in early childhood education - Carolino, Cecília Dutra (2023)
Although the recent expansion of Early Childhood Education in Brazil suggests acknowledgement of the importance of this phase for human and socioeconomic development, the literature shows that having access to low-quality daycare centers can be detrimental to children. Moreover, the public understanding of what constitutes educational quality remains limited. Family-school relationships are typically characterized by the principal-agent problem, which leads to parental misinformation and affects their early investments on children. This work investigates whether greater school openness affects families\' perceptions of educational quality and its distance from objective quality measures. Using novel data from eleven municipalities from the Brazilian state of Ceará, a school openness measure is computed through a split-sample approach to estimate logit and linear distance models. Results show that more openness reduces the probability of families\' being satisfied with health and hygiene aspects, and tend to significantly decrease the distance between parental perceptions and real quality in terms of the visibility of children\'s activities and the quality of materials and toys. Further, caregivers who claim to be highly overloaded by motherhood have increased probability of being satisfied with most educational aspects. These findings suggest that policies aiming at improving parental engagement in schools can be considered as a potential mechanism to mitigate circular informational asymmetry issues.